2012
DOI: 10.1155/2013/834656
|View full text |Cite
|
Sign up to set email alerts
|

1‐Methyl‐3‐(2‐(sulfooxy)ethyl)‐1H‐imidazol‐3‐ium Chloride as a New and Green Ionic Liquid Catalyst for One‐Pot Synthesis of Dihydropyrimidinones under Solvent‐Free Condition

Abstract: An efficient and simple method for the preparation of 1-methyl-3-(2-(sulfooxy)ethyl)-1H-imidazol-3-ium chloride{(MSEI)Cl}as an acidic ionic liquid is described. One-pot multicomponent condensation of 1,3-dicarbonyl compounds, urea/thiourea and aldehydes at 80∘C affords the corresponding compounds in high yields and in short reaction times by using (MSEI)Cl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…For easy handling, we add silica gel to IL 5. The IR spectrum of IL 4, 22 and 5 are compared. The peak at 2060 cm −1 is related to group SCN, and it was shown that novel IL containing thiocyanate ion has been formed ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For easy handling, we add silica gel to IL 5. The IR spectrum of IL 4, 22 and 5 are compared. The peak at 2060 cm −1 is related to group SCN, and it was shown that novel IL containing thiocyanate ion has been formed ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Unreacted 1-methylimidazole or 2-chloroehanol extracted with ether (3 × 10 mL) was used to give 1-methyl-3-(2-hydroxylethyl)-imidazolium chloride (Scheme 1, step 1) (yield 95%). 22 A stoichiometric amount of 97% chlorosulfonic acid (3.4 mL, 50 mmol) in CCl 4 (10 mL) was added dropwise to compound 3 over a period of 45-60 min at 0 • C, afterward, HCl gas was evolved in an alkali trap immediately. The mixture was washed with CCl 4 (3 × 10 mL) to remove the unreacted chlorosulfonic acid and at last the 1-methyl-3-(2-(sulfooxy)ethyl)-1H-imidazol-3-ium chloride ([Msei]Cl) is formed (yield 92%).…”
Section: Discussionmentioning
confidence: 99%
“…In continuation of our study on application of solid acid [26][27][28][29][30][31][32][33][34][35] , we report the synthesis of 14Hdibenzo [a,j]xanthene derivatives in the presence of a catalytic amount of [2-(sulfooxy)ethyl] sulfamic acid (SESA) as a novel, efficient and recycle eco-friendly organo solid acid catalyst in solvent-free condition by a simple, efficient and high-yielding method (Scheme 1). The reaction conditions were optimized on the basis of the catalysts and temperature ( Table 2 and Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…This reaction was easy and clean because HCl gas was evolved from the reaction vessel immediately (Scheme 2). We examined the catalytic ability of SiO 2 /HO 3 SOCH 2 CH 2 NHSO 3 H for thiocyanation regioselectivity reaction to corresponding thiocyanonated compounds N-SiO 3 H. SESA was similarly produced as in our previous report [37][38][39][40]. The product was identified by its spectral data.…”
Section: Resultsmentioning
confidence: 99%
“…Because of these problems and the recent intense attention to environmentally benign protocols, the search for new and efficient catalysts that are able to promote organic reactions under green conditions is of interest for the production of aryl thiocyanates. In continuation of our study on application of solid acid [35][36][37][38][39][40][41][42], we report the synthesis of organothiocyanate derivatives in the presence of a catalytic amount of [2-(sulfooxy)ethyl]sulfamic acid (SESA) as a novel, efficient, and recyclable organosolid acid catalyst in ethanol/water (Scheme 1).…”
Section: Journal Of Catalystsmentioning
confidence: 99%